ALIH KODE DAN CAMPUR KODE BAHASA WOLIO KE DALAM BAHASA INDONESIA DI SATUAN KERJA PERANGKAT DAERAH KOTA BAUBAU - Muliani, Eva; M. Said, Ikhwan; Abbas, Asriani (JURNAL ILMU BUDAYA, 2021)
This study aims (1) to explain the code-switching and mixing of the Wolio language code into Indonesian in the regional work units of the City of Baubau and (2) to reveal the factors that cause code-switching and mixing the Wolio language code into Indonesian in the work unit. Baubau City regional apparatus. The type of research used is descriptive qualitative which describes or depicts the facts of the empirically alive situation of its speakers. The results of this study indicate that there is code-switching and code-mixing in the communication that occurs between the community and employees who work in the regional work units of the City of Baubau. Instead, the code is sorted into high to low and low to high code-switching.